A novel method to identify an intramural segment in interarterial anomalous coronary arteries on CT-angiography. (3rd October 2022) - Koppel, C J; Verheijen, D; Kies, P; Egorova, A D; Lamb, H J; Voskuil, M; Jukema, J W; Koolbergen, D R; Hazekamp, M G; Schalij, M J; Jongbloed, M R M; Vliegen, H W
Abstract: Background/Introduction: An anomalous coronary artery originating from the opposite sinus of Valsalva (ACAOS) with an interarterial course can be assessed using Computed Tomography Angiography (CTA) for the presence of high-risk characteristics associated with sudden cardiac death. These features include a slit-like ostium, acute angle take-off, and degree of proximal luminal narrowing. However, no robust CTA criteria currently exist to determine the presence of an intramural segment. Purpose: The aim of this study is to deduct a method to accurately identify an intramural course of interarterial ACAOS on CTA imaging. Methods: All consecutive adult patients with an interarterial ACAOS that were evaluated at the two academic hospitals between January 2010 and July 2019 were screened for inclusion. Inclusion criteria were availability of a preoperative CTA-scan (0.5–1mm slice-thickness) and peroperative confirmation of the intramural segment. Using multiplanar reconstruction of the CTA, the distance between the lumen of the aorta and the lumen of the ACAOS (defined as "interluminal space" (ILS)) was assessed at 2mm intervals along the intramural segment (Figure 1). Results: Twenty-five patients (64% female, mean age 46 years, 88% right ACAOS) were included. Analysis showed a mean ILS of 0.69mm±0.15mm at 2mm from the ostium. At the end of the intramural segment where the ACAOS becomes non-intramural, the mean ILS was significantly larger (1.27±0.29mm, p<0.001) (Figure 2). Interobserver agreement evaluation showed good reproducibility of ILS (intraclass correlation coefficient 0.77, p<0.001). ROC-analysis demonstrated that at a cut-off ILS of ≤0.95mm, an intramural segment can be diagnosed with 100% sensitivity and 84% specificity. Conclusion(s): The ILS is introduced as novel and robust CTA parameter to identify an intramural course of interarterial ACAOS. An ILS of ≤0.95mm is indicative of an intramural segment with 100% sensitivity and 84% specificity. Funding Acknowledgement: Type of funding sources: None.